The aftermaths of acquisition in Indonesia. (15th February 2020) - Syukur, Muhammad; Bungkilo, Dej-anan
Indonesia is entering a new phase of the business competition after the launching of the Government Regulations No. 57 of 2010 about Mergers and Acquisition. A drastic inclination in numbers of acquisition deals indicates that the acquisition is a technique to show power and dignity yet might result in losing focus on improving the operating performance. Therefore, this paper aims to examine the post-acquisition operating performance of acquirer companies. Their financial performances are reflected by financial ratios which are calculated based on the accounting information from the financial statements. Data are gathered from one year to three years prior and following acquisition years and compared the significance using the Wilcoxon signed-rank test. The total population is 322 acquisition transactions. The results show that asset efficiency, the level of debt, and profitability worsen after the acquisition deals, whereas liquidity and stock price are not impacted.